PENGARUH AUDIT TENURE, ROTASI AUDIT, UKURAN KANTOR AKUNTAN PUBLIK (KAP), DAN UKURAN PERUSAHAAN KLIEN TERHADAP KUALITAS AUDIT (Studi Empiris pada Perusahaan Sektor Kesehatan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2024) - Dewi Handayani; Haryanto Haryanto (Diponegoro Journal of Accounting, 2025)
This study analyzes the effect of audit tenure, audit rotation, public accounting firm size, and client firm size on audit quality. In this research, audit quality is proxied by earnings quality, which is measured using discretionary accruals from the Modified Jones Model. The sampling method used is purposive sampling, resulting in a sample of 22 companies with a total of 132 observations during the 2019-2024 period. The data used are secondary data obtained from financial statements and independent auditor reports of health sector companies listed on the Indonesia Stock Exchange (IDX). Data analysis was performed using multiple linear regression using SPSS 27 software. The results showed that audit tenure and public accounting firm size did not have a significant effect on audit quality, while audit rotation and client company size had a significant positive effect on audit quality.